MENINGKATKAN SKILL PERAWAT DALAM MELAKSANAKAN PERAWATAN LUKA PADA PASIEN DIABETES MELITUS KOTA KEDIRI - Karingga, Devangga Darma; Alimansur, Moh (STIKes Santa Elisabeth Medan, 2024)
Diabetes mellitus is a chronic metabolic disease that can cause various serious complications, including diabetic foot ulcers (DFU), which often require intensive treatment and can result in amputation. The global prevalence of DFU reaches 6.3%, with a significant impact on sufferers' quality of life. This community service program aims to improve nurses' skills in caring for diabetic wounds in Kediri City through special training.The methods used in this program include qualitative and quantitative approaches to collect comprehensive data regarding nurses' knowledge and skills before and after training. This program is implemented in several stages: initial survey to identify training needs, development of comprehensive training materials, implementation of theory and practical sessions, as well as program evaluation through pre- and post-training assessments and participant satisfaction surveys.The results show that this training was successful in increasing nurses' knowledge and skills significantly. This increase is manifested in knowledge of how to prevent complications and amputations in DFU patients, as well as high participant satisfaction with the training program. However, obstacles such as limited medical equipment and materials as well as management support in health services still need to be overcome to ensure the continuity and effectiveness of the program in the future.In conclusion, ongoing training is very important to improve the quality of diabetic wound care by nurses, which will ultimately have a positive impact on the outcomes of diabetes patient care.